Platelet indices- evaluation of their diagnostic role in pediatric thrombocytopenias (one year study) - Baig, Mirza Asif (International Journal of Research in Medical Sciences, 2017)
Background: Thrombocytopenias can be categorised into hypoproliferative (group I) & hyperdestructive types (group II) based on their etiology. Platelet indices (MPV, PDW, P-LCR, platelet-crit) can be used to differentiate this type of thrombocytopenias & these are simple, cost-effective, noninvasive & reliable. The main objective of this study was to evaluate the efficiency of platelet indices to differentiate hypoproductive type from hyperdestructive thrombocytopenias. Methods: Automated Hematology Analyzer Sysmex XT-2000i used to assess platelet indices. 100 Cases of thrombocytopenia & age adjusted (similar age group) controls with normal CBC & peripheral blood smears were included in the study. The gender was not taken into account as the ranges of platelet indices are almost the same for boys & girls of similar age groups. Results: The platelet indices of group I was platelet count = (51.8 ± 31.6) x103/mm, MPV = (8.5 ± 1.27) fl, PDW = (14.10 ± 1.15) fl, P-LCR = (31.90 ± 3.46)%. The platelet indices of group II was platelet count = (39.6 ± 32.7) x103/mm, MPV = (11.6 ± 2.25) fl, PDW = (15.16 ± 1.36) fl, P-LCR = (34.30 ± 2.2)%. Comparative analysis of MPV, PDW & P-LCR of group I and group II showed p value <0.05 proving it to be statistically significant. Conclusions: The combined interpretation of MPV, PDW & P-LCR by automated cell counters can be very useful parameters in differentiating thrombocytopenias due to various etiologies. Platelet indices showed inverse relationship with platelet count as they are increased in hyperdestructive type & shows linear relationship in hypoproliferative type. MPV, PDW & P-LCR can be precisely used to differentiate hyperdestructive type (ITP) from hypoproliferative type (acute leukemias, aplastic anemias). Platelet-crit & platelet large cell ratio are less sensitive parameters to differentiate these thrombocytopenias.